KAJIAN PENGARUH JENIS JAHE (Zingiber officinale Rosc.) DAN WAKTU PENGERINGAN DAUN TERHADAP KAPASITAS ANTIOKSIDAN SERTA SENSORIS WEDANG UWUH - Danthiswara Gelgel, Kadek; Yusa, Ni Made; Mayun Permana, I Dewa Gede (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 2 (2016): Jurnal ITEPA)
This research has conducted to determine the effect of ginger types ( Zingiber officinale Rosc.) increment and drying time of leaves to antioxidant capacity of wedang uwuh. This research used factorial randomized block design, each treatment repeated twice to get 18 result of experimental units. The data was analyzed using analysis of variance and if there was real effect, it would be followed by Duncan test. This research using 3 kinds of ginger types, that are small ginger, red ginger, giant ginger and drying time of leaves (nutmeg leaves, clove leaves, and cinnamon leaves) that are 1 hours, 2 hours, and 3 hours. The result of this research showed that the interaction between type of ginger and drying time of leaves gave an impact to the total phenolic, antioxidant capacity, color, aroma, flavor and overall acceptance towards wedang uwuh . The best result obtained by red ginger and 2 hours drying time of leaves with total phenolic 88.36 mg/kg; antioxidant capacity 112.22 mg/kg GAEAC; sensorys test such as color, flavor, aroma and overall acceptance that liked by the panelists.
Keywords: Type of ginger, drying time, antioxidant, wedang uwuh